The Stylistic Characteristics of Remarks in William Saroyan’s Dramas - Ter-Minasyan, Ashot (Bulletin of Yerevan University B: Philology, 2024)
From the thirties of the 20th century and especially from the middle of the 20th century, great changes were made in dramatic works by the representatives of the French anti-theatre or the theater of the absurd and the American-Armenian writer-playwright William Saroyan, especially the role and content of remarks were expanded. Despite some similarities, the remarks of the theater of the absurd and Saroyan's dramas are essentially different. If time, the clock, the street, the walls of the room became the acting heroes in the first ones, then in the remarks of Saroyan's plays, the emphasis is on the psychology of the heroes and the discovery of their inner world.His remarks stand out for the peculiarities of character creation and image creation, for their philosophical depth and lyricism, thanks to their mastery of bringing the dramatic poem closer to the artistic prose. Saroyan's play notes are replete with subtle uses of gradation, personification, metaphor, comparison, and other means of expression.The remarks-prologues of his plays and the descriptions of the heroes, even their portraits, play the role of a unique pre-plot, preparing the reader for a deeper understanding of the actions themselves. Saroyan's speech art, in particular the content and style features of the remarks of dramas, from the middle of the 20th century, also found a great response in the plays of Armenian authors Hrant Matevosyan, Zorayr Khalapyan, Perch Zeytuntsyan, Kariner Khodikyan, and others.
Keywords: dramaturgy; theater; prose; theater of the Absurd; Arthur Adamov; Samuel Beckett; William Saroyan; Remarque; style; word choice; image; comparison; metaphor; gradation; lyricism